Web Based Data Collection, Transmission and Reporting System - Omoro, Gonza Otieno (JOOUST, 2015)
Web based data collection, transmission and reporting s stem is a project that was aimed at providing a robust mobile application environment that can be used for any study data collection, specifically improving the data collection, transmission and reporting processes of Families latter! Program conducted by KEMRICDC program in the greater Siaya county. This project intended to develop a web based solution to collect and transmit data real time from the field where study facilitators conduct their sessions and also give feedback to the users. Currently KEMRICDC Families Matter! Program uses paper based methods to collect data after which the papers ie case report forms and transported to their data center for processing. This I ads to many challenges in getting accurate, reliable, timely, consistent data that can aid decision making. Completing the forms takes much time. Errors are introduced in the process of transcribing the form into the computer systems compromising the data integrity. Data loss due to transportation issues also arises, due to the fact that tracking manual systems is hectic. The proposed system was analysed and designed using object oriented methodologies. The development was done in three phases, the client side, the middle ware and the server side. The client side tools comprised of HTML, Cascading Styling Sheets, jquery, API, some javascript for validations and also using the POST and GET function to push data. The middle tier consisted of PHP codes together with web service, Apache tomacat was used. The data layer which consisted of MySQL Relational Databases management system to store and manipulate the data. An SMS gateway was used to send sms notifications to the supervisor upon data submission. Functional and user acceptance testing was run to establish defect and also to gain user confidence in the project. The application was implemented using parallel approach which the best since it was important to evaluate the proposed system was working compared to the old systems of collecting the same data. Both the old and the new proposed system were used currently. From the testing and implementation phases this project established that the manual process of data collection was eliminated, data of high integrity was collected and also a user friendly application was developed. Significant time was saved by the solution, errors were reduced, and costs that were earlier on invested in the entire process were saved for other purposes. Feedback too was real time whenever required. This project concludes that data collection being a critical aspect of any research activity should be looked very keenly, and technology should be utilized to make it successful. This project should be later improved to collect multimedia data which was not the scope of this project but very critical in data collection.
Keywords: Web Based Data Collection